PENGARUH MANAJEMEN TENAGA PENDIDIK TERHADAP HASIL BELAJAR SISWA SMA YA BAKII 01 KESUGIHAN - Rohayatun, Fitri Nur (Jurnal Tawadhu, 2022)
This study discusses the description of the management of teaching staff at SMA YaBakii 1 Kesugihan, how is the description of the learning outcomes of class XI students at SMA Ya Bakii 1 Kesugihan and is there any influence between the Management of Educators on the Learning Outcomes of Class XI students at SMA Ya Bakii 1 Kesugihan. The instruments used are questionnaires and documentation about the influence of teacher management on student learning outcomes. The analytical technique used is descriptive statistical analysis technique to answer the categorization of the variable management of educators and student learning outcomes. Then, the inferential statistical analysis technique was carried out to determine whether there was an influence of teaching staff management on the learning outcomes of class XI students at SMA Ya Bakii Kesugihan. Based on the results of descriptive statistical analysis, the implementation of teaching staff management and student learning outcomes is at a moderate level. The results of inferential statistical analysis stated that there was a significant and positive influence between the management of teaching staff on student learning outcomes. It was found that tCount = 3,366 with a significant level of 5% and tTable = 2,110. This means that 3,366 > 2,110 and so it can be concluded that H0 is rejected and Ha is accepted. From these results, it means that there is a significant influence between the management of teaching staff on the learning outcomes of class XI students at SMA Ya Bakii 1 Kesugihan.